LEUKEMIA MEGAKARIOBLASTIK AKUT PADA SEORANG ANAK - Nyoman Suci Widyastiti; Ima Arum Lestarini; Yetty Movieta Nancy; Umi S Intansari; R. Lindeman (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2008)
Acute Megakaryoblastic Leukemia (FAB AML M7) occurs in all age groups with two peaks in distribution. The one is in adults and theother in children 1 to 3 years of age especially in those with Down’s syndrome. The diagnosis of AML M7 requires more than 30% of thenucleated bone marrow cells being megakaryoblasts. The AML M7 was under diagnosed before the availability of monoclonal antibodies.The more common types of AML MO-M6 have to be excluded by morphological and cytochemical analysis whereas immunology is neededto exclude ALL. The megakaryocytic nature of the leukemia has to be proven by ultrastructural demonstration of platelet peroxidase or byimmunological demonstration of CD61, CD42, CD41 on the surface of the leukemic blasts. Megakaryocytic/megakaryoblastic leukemiasshow a wide morphologic spectrum. Cytoplasmic blebs and protrusions are the most prominent feature of many cases. The nuclei ofthese cells are round with more finely reticulated chromatin and with prominent nucleoli. The megakaryoblastic nature of these cells canbe suggested by morphology. Cytochemistry is of limited diagnostic value in megakaryoblastic leukemias. Usually it is used to excludethe more common types of leukemia. An eighteen months girl was admitted to hospital with anemia and hepatosplenomegaly. There isdismorphic - hypertelorism face and enlargement of neck lymph nodes. The laboratory examination found anemia, hyperleukocytosis with75 % blast cells. Morphologically the blast cells show prominent blebs and cytoplasmic budding resemble features of budding platelets.The cytochemistry staining for granulocyte and erythrocyte lineages were negative. The expressions of lymphoid and myeloid lineagesmarkers by immunoflowcytometry method were also negative. Cytogenetic examination was followed. The physical and laboratoryexamination result conclude a child with Acute Megakaryoblastic Leukemia. Cytogenetic examination was followed